2013
DOI: 10.1080/15588742.2012.739132
|View full text |Cite
|
Sign up to set email alerts
|

Foster Care Alumni and Funding for Postsecondary Education: Examining Variation in State Support

Abstract: Recent modifications to the Foster Care Independence Act have enabled states to provide Education and Training Vouchers (ETVs) to foster care alumni who are enrolled in postsecondary education institutions. This article is a summary in which we examine the disparities in states' allocations for ETVs, as well as the variation in states' implementation of broad-based, state-funded tuition waivers. The outcomes are descriptive in nature and display the wide range in ETV funding across the United States; outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Youth aging out of care may transition to independent adulthood with mere perfunctory safety nets (Bellamy, ; Courtney & Heuring, ; Shirk & Stangler, ; Simmel, Shpiegel, & Murshid, ), despite a sustained need for support (Avery & Freundlich, ; Osgood, Foster, & Courtney, ). Many youth in their final years of care have low rates of academic achievement and a high risk of adversity (Goodkind, Schelbe, & Shook, ; Keller, Cusick, & Courtney, ).…”
Section: Introductionmentioning
confidence: 99%
“…Youth aging out of care may transition to independent adulthood with mere perfunctory safety nets (Bellamy, ; Courtney & Heuring, ; Shirk & Stangler, ; Simmel, Shpiegel, & Murshid, ), despite a sustained need for support (Avery & Freundlich, ; Osgood, Foster, & Courtney, ). Many youth in their final years of care have low rates of academic achievement and a high risk of adversity (Goodkind, Schelbe, & Shook, ; Keller, Cusick, & Courtney, ).…”
Section: Introductionmentioning
confidence: 99%
“…This includes the types, quality, and dosage of IL services a youth receives, and the specific ETV amount disbursed to a youth (in combination with other sources of aid). Research has found that many students may not have access to ETVs or FICA-funded programs (Okpych, 2015; Okpych et al, 2020; Simmel et al, 2013). Future research should explore how states are utilizing FCIA funding and how that is related to youth connectedness.…”
Section: Discussionmentioning
confidence: 99%
“…Further, difficulties in monitoring IL programs have persisted across states, but have recently improved with the development of the National Youth in Transition Database (NYTD). Research on ETVs has shown considerable variation in ETV use and expenditures across states (Simmel et al, 2013), and early findings suggest that ETV receipt increases the odds of first-year college persistence (Okpych et al, 2020).…”
Section: Policies Targeting Postsecondary Education and Employment Am...mentioning
confidence: 99%